Structural and Functional Approaches in Arabic Linguistics / المقاربات البنيوية والوظيفية في اللسانيات العربية - Mark Schneider; Aisyah Rahma (IJAS: International Journal of Arabic Studies, 2026)
This study explores structural and functional approaches in Arabic linguistics in order to provide a comprehensive understanding of the Arabic language from both formal and communicative perspectives. The research aims to describe the main characteristics of structural analysis in Arabic linguistics, examine the role of functional perspectives in explaining language use in communication, and highlight the integration of both approaches in analyzing Arabic linguistic phenomena. This study employs a qualitative descriptive method based on literature analysis, examining key works in modern linguistics and Arabic language studies. The findings indicate that the structural approach focuses on the internal system of language, including phonology, morphology, and syntax, while the functional approach emphasizes the communicative role of language in social contexts. Furthermore, the study shows that combining structural and functional perspectives provides a more comprehensive analytical framework for understanding Arabic linguistic structures and their communicative functions. The study concludes that the integration of these two approaches can significantly contribute to the development of Arabic linguistic research and enhance the effectiveness of Arabic language teaching and analysis in contemporary linguistic studies.